ANALISA VISUAL MOTIF POLENG PADA DODOTAN BIMA WANDA LINDU PANON JOGJAKARTA - Rizki Putri Rezna Hassan (ATRAT: Jurnal Seni Rupa, 2015)
This research aim is to divulge the idea of poleng pattern on one of the famous shadow puppet’s character, Bima. The research took a sample of Bima when he was in the condition of wanda lindu panon which origin is from Jogjakarta. The analysis of this research used the format of art critic’s writing method which is correlated with the completio oppositorum theory. In this research, also, has the explanations about the history of Bima in shadow puppet of Java, the overall visualization of Bima in wanda lindu panon, the format of wanda lindu panon on Bima Jogjakarta, the details of under outfit on Bima Lindu Panon, and dodotan on Bima Jogjakarta in wanda lindu panon. On the other hand, this research is also explains the origin of poleng pattern and its correlation with the system of beliefs in the society of Bali and the theory of completio oppositorum. All in all, this research leads to a conclution which the meaning of poleng’s pattern usage on Bima Jogjakarta in wanda lindu panon is for spiritual necessity.Keywords: Bima, Wanda, Shadow Puppet, Poleng___________________________________________________________________Penelitian ini bertujuan untuk mengungkap makna dari motif poleng pada pakaian salah satu tokoh pewayangan terkenal, yaitu Bima. Sampel yang diteliti merupakan tokoh Bima dalam kondisi wanda lindu panon yang berasal dari Jogjakarta. Analisa dalam penelitian ini menggunakan metode penulisan kritik seni dikaitkan dengan teori Completio Oppositorum. Pada penelitian ini dijelaskan mengenai sejarah tokoh Bima pada pewayangan Jawa, visual Bima wanda lindu panon secara keseluruhan, pakem pada wanda lindu panon Bima Jogjakarta, detail pakaian bagian bawah Bima lindu panon, dan dodotan pada Bima Wanda Lindu Panon Jogjakarta. Selain itu, penelitian ini juga membahas asal usul motif poleng serta kaitannya dengan sistem kepercayaan masyarakat Bali dan teori Completio Oppositorum. Penelitian ini berujung pada kesimpulan bahwa penggunaan motif poleng pada Bima wanda lindu panon jogjakarta bermakna spiritual.Kata Kunci: Bima, Wanda, Wayang, Poleng